(untitled) (2003)
A method for the removal of trace amounts of mercury (II) using aluminium hydroxide as the collector. Dithizone in carbon tetrachloride was used for the extraction of mercury. The amount of Hg (II) wasvaried from 40 mg to 100 mg. The sample volume was varied until 50ml and the level of extraction of mercury was recorded. It was found that the recovery was satisfactory until a sample volume of 25 ml,beyond which the recovery gradually decreased. The effect of interfering ions was studied at different concentrations of mercury and was found to be minimum.